Determine the Various Types of Fungi Found on Corpse - A Review - Sakshi A. Kharmate,; Patima N. Yadav, (International Journal of Scientific Research in Science and Technology, 2024)
This is the first overview to be published of the whole field of forensic mycology. It is based on all available information located in the literature. Information on fungi is given, and this is followed by an outline of the value, and potentially wide application, of mycology in criminal investigation. Applications include roles in providing trace evidence; estimating time since death (post-mortem interval); ascertaining time of deposition; investigating cause of death, hallucinations, or poisonings; locating buried corpses; and biological warfare. Previous work has been critically evaluated, with particular attention to its evidential value, and suitability for presentation in a court of law. The situations where mycology might assist an investigation are summarized, and issues relating to the further development of the subject are presented. A comprehensive bibliography with 120 citations is provided.
Keywords: Mycology; Fungi; Criminal Investigation; Postmortem; Poisoning